E&M coding clear & simple : evaluation & management coding worktext - Brame, Terri (F.A. Davis, 2014)
Everything you need for E&M coding success! Master the most widely used and most important codes in professional practice with a simple, systematic framework that shows you how to assign E&M codes accurately. You'll build a solid understanding of the core concepts you need to know in practice, and then discover the different types of E&M codes and when to use them. A wealth of tools guides you every step of the way. Critical-thinking and focus questions sharpen your analytical skills. Flow charts break the decision-making process into bite-size pieces. "Communicating With Medical Providers"
Keywords: Clinical medicine -- Code numbers; Health insurance claims -- United States; Nosology -- Code numbers